Implementation of E-Module Development Based on Canva Application on Data Presentation Material to Improve Mathematics Learning Outcomes of MTsN Kota Kupang Students - Akbar, Fitri Ramadani; Garak, Siprianus Suban; Rimo, Imelda Hendriani Eku (Electronic Journal of Education, Social Economics and Technology, 2024)
Education in the current era, especially in the field of Education in terms of teaching applied at school. The improvement of 21st century learning to improve learning outcomes, the ability to analyze, think critically, creatively and problem solving skills. This is seen with many teaching problems in the classroom, with the presence of e-module digitized learning can be an effective learning innovation. The purpose of this research is to support the progress of the learning process in advancing learning activities and student learning outcomes in mathematics learning. The target to be obtained is to produce a Canva-based digital e-module product. Thise-module discusses data presentation material. The use of this Canva application helps to design learning as a support for students' independent learning resources that are easily accessible. The research method used is research and development (RD). The focus in developing digital history teaching materials uses the ADDIE development model, namely: analysis, design, development, implementation, and evaluation using non-test methods in the form of questionnaires. The feasibility test was conducted by media experts, material experts, and students. The results showed sig. 0.02, which means that there is an effect of e-modules to improve student learning outcomes in mathematics learning.